RETRACTED ARTICLE: MicroRNA-29 mediates anti-inflammatory effects and alleviation of allergic responses and symptoms in mice with allergic rhinitis - Jia Wang; Jinshu Yin; Hong Peng; Aizhu Liu (Allergy, Asthma & Clinical Immunology, 2021)
Abstract Background To investigate the role of microRNA-29 (miR-29) in mice with allergic rhinitis (AR) and its underlying mechanism. Methods AR model was established in BALB/c mice by intraperitoneal sensitization and intranasal challenge with ovalbumin (OVA). miRNA expression was examined in the nasal mucosa tissues of mice and patients with AR, and miRNA-29 was found to be downregulated. To unveil the role of miRNA-29 in AR, it was overexpressed in the nasal mucosa of AR mice by intranasal administration of miRNA-29 agomir. The symptoms of nasal rubbing and sneezing were recorded and evaluated. miR-29 expression, OVA-specific immunoglobulin E (IgE) concentration, pro-inflammatory cytokines levels, eosinophils number, and cleaved caspase-3 and CD276 expression were examined in nasal mucosa tissues and nasal lavage fluid (NALF) by qRT-PCR, ELISA, hematoxylin and eosin staining, western blotting, or immunohistochemistry, respectively. TUNEL assay was used to analyze nasal mucosa cells apoptosis. Results Decreased expression of miR-29 was observed in AR, the symptoms of which were alleviated by overexpressing miR-29. In addition, overexpression of miR-29 markedly reduced the concentration of OVA-specific IgE, the levels of IL-4, IL-6, IL-10, and IFN-γ, the pathological alterations and eosinophils infiltration in the nasal mucosa. Furthermore, restoration of miR-29 expression reduced nasal mucosa cell apoptosis. Moreover, overexpression of miR-29 significantly attenuated CD276 mRNA and protein levels in nasal mucosa cells. Conclusion MiR-29 mediated antiallergic effects in OVA-induced AR mice by decreasing inflammatory response, probably through targeting CD276. MiRNA-29 may serve as a potential novel therapeutic target for the treatment of AR.